Prevalence and heritability of psoriasis and benign migratory glossitis in one Brazilian population - Maria Augusta Jorge; Heron Fernando de Sousa Gonzaga; Jane Tomimori; Bruna Lavinas Sayed Picciani; Calógeras Antônio Barbosa (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Background: An oral condition associated to psoriasis is benign migratory glossitis. The review of the literature does not show any publication about heritability in both soriasis and benign migratory glossitis and prevalence of psoriasis in the Brazilian population. Objective: This research was carried out in order to determine the prevalence of psoriasis and benign migratory glossitis in the Brazilian population from a Brazilian sample, as well as the heritability in these conditions. Methods: Six thousand patients were studied from the records of the outpatient dermatology department. The sample had 129 patients with cutaneous psoriasis, 399 with benign migratory glossitis without psoriasis and a control group with 5,472 patients. After data collection, the statistical analysis was made using Woolf, Chi-square and Falconer tests. Results: The prevalence of psoriasis was 2.15% and the benign migratory glossitis was 7.0%. The prevalence of benign migratory glossitis in the psoriasis group was high (16.3%), and that was statistically significant. Family history in the psoriasis group was 38% for the condition itself and 2,75% for benign migratory glossitis and in the benign migratory glossitis group was 17.54% for the condition itself and 1.5% for psoriasis. The study of heritability was 38.8% for psoriasis and 36.6% for benign migratory glossitis, both with medium heritability. Study limitations: This study was only in the state of São Paulo. Conclusion: This is the first publication that quantifies how much of these conditions have a genetic background and how important the environmental factors are in triggering them.